Phase behaviour of gelatin/polydextrose mixtures at high levels of solids - Almrhag, O.; George, P.; Bannikova, A.; Katopo, L.; Chaudhary, Deeptangshu; Kasapis, S. (Elsevier, 2012)
This investigation focuses on understanding the phase behaviour of gelatin when mixed with polydextrose (co-solute) primarily at high solid concentrations. The experimental work was carried out using small deformation dynamic oscillation in shear, modulated differential scanning calorimetry, Fourier transform infrared spectroscopy, wide angle X-ray diffraction and environmental scanning electron microscopy. A progression in the mechanical strength and thermal stability of the gelatin network was observed with the addition of polydextrose to the system. Combined thermomechanical and microscopy evidence argues for the development of phase separation phenomenon between protein and co-solute in high-solid preparations, where gelatin maintains helical conformation to provide network integrity as well as glassy consistency at subzero temperature. At the high solids regime, glassy consistency was treated with theoretical frameworks from the synthetic polymer research to pinpoint the glass transition temperature of the system.